Mulch versus brash: a case study of in situ harvesting residue treatment and its effects on C and nutrients in soil and plant uptake during natural rewilding - Rona M. Pitman (Elsevier, 2021)
Western hemlock brash decay was investigated over seven years on a UK lowland clay soil site, clear-felled in 2002 for broadleaf restoration. Two brash loadings (9.3 (Heavy) and 5.6 (Light) kg m − 2), a chipped mulch (9.4 kg .m − 2), a seeded grass and a bare soil treatment were incorporated in a fenced split block design. In situ decay of Mulch and Brash was followed by field sampling, and a three year litterbag study of needles, twigs and small branch decay. Natural plant recolonisation was followed in repeated ground surveys within each treatment. Heavy Brash residue lost weight through rain leaching, whilst Light Brash and Mulch gained through the action of decay fungi (Basiodiomycete spp) . The N resource in the Mulch residue 2006 (1660 kg ha−1 of N) was twice that of the Heavy Brash in 2005 (748 kg ha−1of N) from similar initial loadings, with subsequent N and C release from the Mulch resulting in significantly higher soil TN and DOC levels. Above ground uptake was determined using allometric relations of birch height: biomass and ground cover: biomass in 2007. N uptake was initially rapid in the seeded grass plots, where soil TN values were significantly the lowest and soil pH the highest of all treatments in 2005 - an indication that sown grass can be an effective sink for leached N after harvesting. Birch (Betula pendula L) subsequently sequestered >75 kg ha−1 of N in the Light Brash treatments with a further 30 kg ha−1 in the shrub/grass under storey by 2007, representing ~28% of the Light Brash residue N resource. N uptake on the Mulch, with < 50% plant cover, represented <3% of the Mulch resource.Conclusions: Mulching brash in situ produced a tidy site, but the deep layer (~14 cm) resulted in an increased resource of N and C in the residue through fungal action, locking up nutrients for three years. Subsequently (yr 4–7) significantly higher levels of DOC and TN were released to the soil, compared to all other treatments. Total mineral soil C and N stock in year 7 was high but not significantly different under Mulch and Heavy Brash, indicating that this excess N was not retained in the topsoil. A deep layer of mulched material cannot be recommended as a treatment for harvesting residue on N sensitive sites, or for rewilding projects where natural plant colonisation is expected.